HOW MANY MILES TO BABYLON? MAPS, GUIDES, ROADS, AND RIVERS IN THE EXPEDITIONS OF XENOPHON AND ALEXANDER*. (25th March 2015) - Unknown
Abstract : When Alexander III of Macedon set out on campaign against the Persian Empire in 334bc, he had little previous experience to draw on in devising the route to follow. Xenophon had covered some of the ground, but his written account took the route in reverse and was notably full of crisis management and extemporizing: it is doubtful whether Alexander made much use of it. Herodotus had described the basic topography of the Persian empire over a century before, but not in much detail. This article considers the kinds of information that Alexander had to draw on in planning his route, and the ways in which he, and Xenophon before him, acquired the information they needed on the way.